Influence of short-term hypoxia exposure on dynamic visual acuity - Wang, Yuchen; Xie, Jiaxing; Yu, Xinli; Liu, Yihe; Wang, Zesong; Guo, Anqi; Ding, Yi; Zhou, Xinzuo; Liu, Siru; Li, Jiaxi; Zhou, Chengkai; Li, Yuanhong; et al. (Frontiers in Neuroscience, 2024)
Background To quantify the changes in dynamic visual acuity (DVA) and explain the hidden reasons after acute exposure to hypobaric hypoxia status. Methods The study group comprised 18 healthy male and 15 healthy female participants aged 20–24 years old. DVA was measured with the self-developed software of Meidixin (Tianjin) Co., Ltd. Measurements were taken at eight altitudes. Data analysis was performed using the Kolmogorov–Smirnov test, paired sample T-test, and two-way repeated measures analysis of variance (ANOVA) for repeated measurements. Results At constant altitude, DVA showed an overall decreasing trend with increasing angular velocity and a fluctuating decrease at the vast majority of altitudes. At constant angular velocities, DVA gradually increased with altitude, with the most pronounced increase in DVA at altitude 5, and thereafter a gradual decrease in DVA as altitude increased. Finally, as altitude decreased, DVA increased again and reached a higher level at the end of the experiment, which was superior to the DVA in the initial state. Conclusion Under a hypobaric hypoxic environment at high altitude, DVA was affected by the angular velocity and the degree of hypoxia, manifesting as an increase or decrease in DVA, which affects the pilot's observation of the display and control interfaces during the driving process, acquisition of information, and decision-making ability, which in turn may potentially jeopardize the safety of the flight.